Influenza Vaccination and Hospitalization Outcomes Among Older Patients With Cardiovascular or Respiratory Diseases. (11th August 2020) - Pang, Yuanjie; Wang, Qi; Lv, Min; Yu, Mengke; Lu, Ming; Huang, Yangmu; Wu, Jiang; Xie, Zheng
Abstract: Background: Influenza vaccination has been suggested to protect against death and recurrent events among patients with cardiovascular disease or chronic obstructive respiratory disease, but there is limited evidence in older adults, who have higher risks of influenza-associated hospitalization and mortality. Methods: Patients aged ≥60 years hospitalized for cardiovascular or respiratory diseases from the Beijing Urban Employee Basic Medical Insurance database during 3 influenza seasons (2013–2014 through 2015–2016) were pooled to estimate the effects of influenza vaccination on hospitalization outcomes. Vaccination status was ascertained through cross-referencing the Beijing Elderly Influenza Vaccination database. The summer months (June–August) were used as a reference period to adjust for unmeasured confounders during influenza seasons. Results: After adjustment for both measured and unmeasured confounders, influenza vaccination was associated with lower risks of in-hospital deaths among patients hospitalized for cardiovascular (odds ratio [95% confidence interval], 0.85 [.68–1.06]) or respiratory diseases (0.66 [.54–.82]). Influenza vaccination was associated with a lower risk of readmission among patients with cardiovascular (odds ratio [95% confidence interval], 0.81 [.69–.95]) but not respiratory diseases (1.12 [.92–1.35]). Influenza vaccination was also associated with lower direct medical costs, but not with length of stay. Conclusions: Influenza vaccination protected against hospitalization outcomes among older adults with cardiovascular or respiratory diseases. Abstract : Influenza vaccination was associated with lower risk of in-hospital death among patients hospitalized for cardiovascular or respiratory disease, lower risk of readmission among patients hospitalized for cardiovascular disease, and lower direct medical costs for both cardiovascular and respiratory diseases.